Characterization of the immune system of Ellegaard Göttingen Minipigs - An important large animal model in experimental medicine - Pernold, Clara P.S.; Lagumdzic, Emil; Stadler, Maria; Mair, Kerstin H.; Jäckel, Sven; Schmitt, Michael W.; Ladinig, Andrea; Knecht, Christian; Dürlinger, Sophie; Kreutzmann, Heinrich; Martin, Vera; Sawyer, Spencer; et al. (Frontiers in Immunology, 2022)
Interest in Ellegaard Göttingen Minipigs (EGMs) as a model in experimental medicine is continuously growing. The aim of this project is to increase the knowledge of the immune system of EGMs as information is still scarce. Therefore, we studied the postnatal maturation of their immune system from birth until 126 weeks of age. For the first 26 weeks of the study, animals were kept under pathogen-reduced conditions (SPF) and afterwards under conventional housing conditions. The development of the immune system was analyzed by monitoring changes in absolute numbers of leukocytes and lymphocytes of ten individuals and the composition of leukocyte populations by multi-color flow cytometry (FCM). We followed the presence of monocytes using monoclonal antibodies (mAbs) against CD172a and CD163 and B cells based on the expression of CD79a. NK cells were distinguished as CD3-CD16+CD8α+/dim cells and further subdivided using NKp46 (CD335) expression into NKp46-, NKp46+, and NKp46high NK cells. T cell receptor (TCR) γδ T cells were defined by the expression of TCR-γδ and different subsets were determined by their CD2 and perforin expression. TCR-αβ T cells were classified by their CD8β or CD4 expression. For monitoring their differentiation, expression of CD27 and perforin was investigated for CD8β+ T cells and CD8α together with CD27 for CD4+ T cells. We clearly detected a postnatal evolution of immune cell composition and identified phenotypes indicative of differentiation within the respective leukocyte subsets. Examination of the development of the antigen-specific immune system after transfer to different distinct housing conditions and after vaccination against common porcine pathogens such as porcine circovirus 2 (PCV2) revealed a markedly increased presence of more differentiated CD8+ and CD4+ T cells with central and effector memory T cell phenotypes. To complement the findings, a PCV2 vaccine-specific antigen was used for in vitro restimulation experiments. We demonstrated antigen-specific proliferation of CD4+CD8α+CD27+ central and CD4+CD8α+CD27- effector memory T cells as well as antigen-specific production of TNF-α and IFN-γ. This study of postnatal immune development defines basic cellular immune parameters of EGMs and represents an important milestone for the use of EGMs for immunological questions in experimental medicine.